pH-Metric Studies of Cu(II) and Th(IV) Complexes with Pyrazolines and Pyrazoles - Jamode, V.S.; D.V. Thakre, Miss (Asian Journal of Chemistry, 2010)
The interaction of Cu(lI) and Th(IV) with 1-(3-chlorophenyl)-3-(2- hydroxy-5-methylphenyl)-5-phenylpyrawline (1), 1-(3-chlorophenyl)-3- (2-hydroxy-3-bromo-5-methylphenyl)-5-phenyl- pyrawline (2) and 1-( 3-pheny Isulphony 1)-3-(2-hydroxy -3-bromo-5-methylphenyl)-5-( 4-methoxyphenyl) pyrazole (3) have been investigated by Bjerrum method as adopted by Calvin and Wilson. The stability constants of complexes of Cu(lI) and Th(IV) have been studied at constant temperature (27 ± 0.1°C) and 0.1 M ionic strength in 70% DMF-water mixture. It was observed that as the colour changes from light brown to darker shade there is complex formation between ligand and metal ion.